2017
DOI: 10.4103/1319-2442.206440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal function in Indian patients with sickle cell disease

Abstract: Sickle cell disease (SCD) and its variants are genetic disorders resulting from the presence of a mutated form of hemoglobin. Renal disease is one of the most frequent complications, and kidney damage starts very early and progresses throughout life causing severe complications. The present study is aimed to analyze creatinine-based estimated glomerular filtration rate (eGFR) in 616 SCD patients (507 HbSS and 109 HbSB+), receiving medical care at outpatient wing of Sickle Cell Institute, Chhattisgarh. Glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…SCD is associated with liver ischemia 41 and kidney impairment. 42 The elevated levels of urea and creatinine in SCD and the effect of HU on these levels are in line with the reported literature. 3,43 Current results indicate that EA had minimal effect for any further improvement in the HU effect on serum glutamic pyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), and urea levels (Figure S8).…”
Section: ■ Discussionsupporting
confidence: 89%
“…SCD is associated with liver ischemia 41 and kidney impairment. 42 The elevated levels of urea and creatinine in SCD and the effect of HU on these levels are in line with the reported literature. 3,43 Current results indicate that EA had minimal effect for any further improvement in the HU effect on serum glutamic pyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), and urea levels (Figure S8).…”
Section: ■ Discussionsupporting
confidence: 89%
“…One of our previous studies demonstrated that most SCA patients exhibit GHF followed by renal insufficiency. Moreover, this study showed that the SCA patients with kidney damage have a higher level of HbF (25). This study revealed that the IL1RN VNTR polymorphism was not found to be associated with kidney damage in SCA patients.…”
Section: Discussionmentioning
confidence: 63%
“…HbF is a major SCD modifier, which is known to modulate the SCD phenotype (Coleman and Inusa, 2007), to ameliorates pathophysiological and clinical manifestations of the sickling process (Adekile, 2020). There is accumulating evidence indicating that this major disease modifier is influenced by β-globin gene cluster haplotypes (Lakkakula et al, 2017;Piel et al, 2017;Adekile, 2020) and (α-globin gene deletions (Piel et al, 2017). Thus, we have looked at distribution of fetal haemoglobin levels vs. representative β-globin gene cluster haplotypes and α-globin gene deletions and results are shown in Figure 4.…”
Section: Distribution Of Hbf Levels Vs β-Globin Gene Cluster Haplotymentioning
confidence: 99%